Penerapan Pembelajaran Blended Learning melalui Team Based Project - Welas Listiani; Rachmawati; Rina Wijayanti; Siti Napfiah; Choirul Kurniawan; Yasinta Y (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
Based on the main work indicator or IKU 7, namely collaborative and participatory through the case method and team based project with a student-centred learning orientation. The Mathematics Education Study Program at IKIP Budi Utomo followed up on this by collaborating in PDK (Collaborative Online Learning) together with the University of Flores through a blended learning scheme. This scheme is based on project based learning which requires students to carry out a project as a team to achieve a solution to a problem. This research is qualitative research. The objects of this research are students of the Mathematics Education Study Program at IKIP Budi Utomo and Flores University who are taking Entrepreneurship courses in the odd semester of the 2023/2024 academic year. Determining the research object was carried out by means of purportive sampling. The instrument used in this research is the researcher as an observer or interviewer. The data collected came from interviews, observations and documentation through FGD (Focus Group Discussion). Team based project learning is carried out using blended learning using a learning managing system. Students receive an Entrepreneurship module in which there are assignments that students must complete. Entrepreneurship learning is carried out using blended learning because it is carried out collaboratively by IKIP Budi Utomo and the University of Flores which does not allow for offline lectures. This is done to create effective and efficient lectures. Based on the results of the research and discussion, it can be concluded that blended learning through team based projects can provide students with experience in being able to think critically, analytically and creatively in solving problems. The team based project approach used in entrepreneurship courses is able to increase student creativity in the business world.